Deformation mechanisms in surface nano-crystallization of low elastic modulus Ti6Al4V/Zn composite during severe plastic deformation. (December 2018) - Lv, Yuting; Ding, Zihao; Xue, Jing; Sha, Gang; Lu, Eryi; Wang, Liqiang; Lu, Weijie; Su, Chunjian; Zhang, Lai-Chang
Abstract: Decreasing elastic modulus and simultaneously improving biological compatibility has been a major challenge in developing biomedical alloy. In this study, Ti6Al4V/Zn composite with surface nano crystallization is successfully fabricated by friction stir processing (FSP) with simultaneous addition of beneficial Zn element. Nanoscale microstructures in surface region include nanoscaled Zn rich particles (including TiZn2 ), α nanograins, nanotwins and nano α + β lamellae. Dislocations slip and grain boundary sliding contribute much to the transformation of α-Ti nanograin, while dynamic overlapping of two partial dislocations is the main deformation mechanism for nanotwins. Interestingly, these nanoscale microstructures reduce the elastic modulus of this region. Graphical abstract: Unlabelled Image